A comprehensive review on EV power converter topologies charger types infrastructure and communication techniques - Vishnuram, Pradeep; R, Narayanamoorthi; P, Suresh; K, Vijayakumar; Bajaj, Mohit; Khurshaid, Tahir; Nauman, Ali; Kamel, Salah (Frontiers in Energy Research, 2023)
The energy transition is a crucial effort from many sectors and levels to create a more integrated, carbon-neutral society. More than 20% of all greenhouse gas emissions are attributed to the transportation sector, predominantly concentrated in metropolitan areas. As a result, various technological hurdles are encountered and overcome. It facilitates the adoption of electric vehicles (EVs) run on renewable energy, making them a practical option in the fight against climate change and the completion of the energy revolution. Recent developments suggest that EVs will replace internal combustion engine (ICE) during the next few months. The EV either gets all of its power from batteries and ultra capacitors or some of it from both. In a plug-in electric vehicle, the battery or ultra-capacitor is charged by an AC supply connected to a grid line. In a hybrid electric vehicle, the ICE charges the battery or ultra-capacitor. Regenerative braking is another way to charge the battery from the traction motor. In a plug-in electric vehicle, the energy from of the battery or ultra-capacitor is put back into the AC grid line. Electronic converters are essential to converting power from the grid line to the traction motor and back again. This paper examines the current state of the electric vehicle market throughout the world and its potential future developments. Power electronics converters (PEC) and energy storage devices significantly impact electric vehicles’ efficiency. Furthermore, general opinions about EVs are soon in this sector, as well as research topics that are still open to industry and University researchers.